Assessment of Mangrove Management Areas in Four Coastal Barangays of Bolinao, Pangasinan, Philippines - Paz-Alberto, Annie Melinda; Teñoso, Annie Rose D. (Silliman Journal, 2022)
This study aimed to assess the diversity of mangroves, fish, and other economically important aquatic species and to determine the physical, chemical and biological characteristics in the mangrove management areas at Balingasay, Arnedo, Victory and Binabalian, Bolinao, Pangasinan in order to evaluate the present condition of these mangrove areas. Based on the assessment made, the municipality of Bolinao has established several projects and programs on the management of the mangrove ecosystems. In the mangrove management areas, 24 mangrove tree species were found with Rhizophora mucronata as the most dominant and densest among the species in each area except in Balingasay where Nypa fruticans was the densest and most dominant. Only 18 fish and invertebrate species were identified from the four mangrove management areas. Polinces aurontius, Trachycardium orbita, and Terebralia polustris had the highest importance value index for the fish and invertebrate species. Diversity index values of mangrove and other marine species in the mangrove management areas are very low. The physical, chemical and biological characteristics of the mangrove ecosystems of Bolinao were found to be of good water quality being within the optimum level set by the DENR for marine species to thrive and replenish. However, all the mangrove ecosystems obtained high total coliform and Barangay Balingasay got also high fecal coliform which are attributed to domestic wastes. The mangrove management areas still have low diversity of mangroves and other marine species and high total and fecal coliform due to human activities. Hence, for the attainment of sustainability of the mangrove management areas, it is imperative that there should be a strong cooperation, coordination and involvement among the key stakeholders such as local and national government and the local community to address the issues and problems present in the mangrove areas.